Injury surveillance in taekwondo and judo during physiotherapy coverage of the seventh all Africa Games - J. S. Phillips; J. M. Frantz; S. L. Amosun; W. Weitz (AOSIS, 2001)
Objective: To obtain data relating to the incidence of injuries sustained during taekwondo and judo competitions at the 7th All Africa Games. Methods: Prospective recording of injuries sustained by athletes who sought physiotherapy services at the games. Details of type of injury, injury sites and injury severity were obtained. Results: Seventy athletes out of 390 participants reported injuries. The overall injury risk ratio was 0.18. Injuries reported were strains/sprains (65,6%), bruises/contusions (16.1%) and dislocations or fractures (12,9%). The upper limbs were more commonly injured. Of the injuries sustained, approximately 18%, 69% and 13% were respectively classified as mild, moderate and severe injuries. Conclusions: The high incidence of moderate to severe injuries highlights the need for injury prevention programs and the presence of medical staff at major tournaments in order to make early diagnosis and appropriate intervention.